Renovation of Public Buildings towards nZEB: A Case Study of a Nursing Home - Mihaela Teni; Ksenija Čulo; Hrvoje Krstić (Buildings, 2019)
Recently, the European Union set new rules for the Energy Performance of Buildings emphasizing the need to facilitate the cost-effective renovation of existing buildings into nearly zero-energy buildings (nZEB). Within this framework, the aim of this paper is to investigate and evaluate the energy performance of existing public buildings before and after renovation into nearly zero-energy buildings. Since the general quality of existing buildings in Croatia has changed over different periods of construction, the presented research was conducted on a representative nursing home designed corresponding to different Croatian national building stock construction periods, based on a public sector buildings database obtained from the Croatian Energy Management Information System (EMIS). The thermal performance of the building envelope was designed to correspond to the periods of buildings built up to 1940, between 1941 and 1970, and between 1971 and 1980, taking into account characteristic building construction technology and service life. In terms of adopted energy efficiency measures, for all nearly zero-energy building renovation solutions, an energy and cost analysis was performed. The results showed that construction technology applied in different construction periods has the greatest impact on the energy performance of a building and thus on the economic and financial viability of investment in nZEB.